Language Mapping of the Cordillera Administrative Region Using Relational Model - Miguel, Dalos D.; Andres, John Austin T.; Batara, Heidi F.; Bautista, Raquel S.; Gavino III, Leonardo B.; Laroya, Karl Adrian G.; Mercado, Rodolfo Aaron E.; Policarpio, Rianne Justin R.; Videz, Graeven Yuri B. (International Journal of Computing Sciences Research; Vol 8 (2024): Volume 8, 2024)
Purpose – Various studies have already done the language mapping of the different languages of the Philippines, though it only consists of the most popular languages per region. Specifically for the Cordillera Administrative Region (CAR), there is a lack of studies regarding mapping its indigenous languages to their respective communities. Resources and data about its languages are also insufficient, contributing to the language barrier problem. Method – The study created a relational model containing CAR’s languages mapped to their respective communities, along with a translation of prevalent phrases, which are used in a language mapping application. The data was collected from online sources and the Philippine Statistics Authority (PSA). Native speakers of the languages involved were also sought after to translate prevalent phrases into their respective languages. Results – The relational model revealed that there are 22 languages spoken in CAR. The developed language mapping application displayed CAR's provinces, municipalities, languages, dialects, and translated phrases from specific languages to enable users to gain new insights about the region. Conclusion – The study was able to create a functional prototype that can present information about the different provinces of CAR, especially its indigenous languages. Through the prototype, the study has shown the importance of preserving CAR’s cultural heritage. Recommendations – Future studies are recommended to further understand CAR’s linguistic landscape. Further research about other Philippine regions’ linguistic landscape is also recommended. To do so requires more data to be collected about commonly spoken languages and their dialects. Research Implications – The created prototype may benefit tourists in knowing more about CAR and its indigenous languages by presenting information and language translations of the region. The study may also benefit future researchers and aid in preserving CAR’s culture.